P020 Reduced duration and continuity of N3 sleep is associated with excessive daytime sleepiness in suspected obstructive sleep apnea patients. (7th October 2021) - Chen, X; Korkalainen, H; Leppänen, T; Oksenberg, A; Töyräs, J; Terrill, P
Abstract: Introduction: Excessive daytime sleepiness (EDS) is a common but not universal-accompanying symptom of obstructive sleep apnea (OSA). The mechanisms explaining the presence of EDS in OSA subjects are not fully understood. We hypothesised that characteristic differences in sleep architecture can be quantified with more comprehensive descriptors of sleep continuity in those with and without severe-EDS according to the Multiple Sleep Latency Test (MSLT). Methods: 2111 participants with suspected OSA and complaints of daytime sleepiness underwent in-lab diagnostic polysomnography (PSG) and next-day MSLT. Sleep continuity was quantified by calculating the cumulative-frequency relationship of continuous sleep-state duration against proportion of sleep time; and continuous sleep-state duration against absolute sleep time. Results: Study contained 368 severe-EDS participants (MSLT≤5min) and 385 non-EDS participants (MSLT>15min). Severe-EDS participants had less Wake After Sleep Onset (48.1±37.7 vs. 68.1±44.2-minutes, p<0.05 [mean±SD]), and greater Total Sleep Time (366.5±50.3 vs. 336.2±58.2-minutes, p<0.05). While total NREM sleep time was similar between groups, severe-EDS participants had less N3 sleep (67.7±38.0 vs. 78.6±32.0-minutes, p<0.05) and more N2 sleep (230.7±59.3 vs. 178.4±45.9-minutes, p<0.05). Moreover, severe-EDS participants had both less cumulative N3 sleep (36.9±2.9 vs. 60.0±3.3-minutes, p<0.05) and a lower proportion of N3 sleep (66.8±5.3% vs. 77.2±4.2%, p<0.05) occurring in periods ≥10mins duration. Discussion: Whilst OSA participants with severe EDS have similar NREM sleep time to non-EDS participants; they have less N3 sleep, and N3 sleep periods are less consolidated. These preliminary results suggest that individuals with OSA which disturbs both the quantity and consolidation of N3 sleep are at greater risk of severe EDS.